Proceedings From the Ice Hockey Summit III: Action on Concussion. Issue 3 (May 2021) - Smith, Aynsley M.; Alford, Patrick A.; Aubry, Mark; Benson, Brian; Black, Amanda; Brooks, Alison; Burke, Charles; D'Arcy, Ryan; Dodick, David; Eaves, Michael; Eickhoff, Chad; Erredge, Kristen; et al.
Abstract : Objectives: The Ice Hockey Summit III provided updated scientific evidence on concussions in hockey to inform these 5 objectives: (1) describe sport related concussion (SRC) epidemiology; (2) classify prevention strategies; (3) define objective, diagnostic tests; (4) identify treatment; and (5) integrate science and clinical care into prioritized action plans and policy. Methods: Our action plan evolved from 40 scientific presentations. The 155 attendees (physicians, athletic trainers, physical therapists, nurses, neuropsychologists, scientists, engineers, coaches, and officials) voted to prioritize these action items in the final Summit session. Results: To (1) establish a national and international hockey database for SRCs at all levels; (2) eliminate body checking in Bantam youth hockey games; (3) expand a behavior modification program (Fair Play) to all youth hockey levels; (4) enforce game ejection penalties for fighting in Junior A and professional hockey leagues; (5) establish objective tests to diagnose concussion at point of care; and (6) mandate baseline testing to improve concussion diagnosis for all age groups. Conclusions: Expedient implementation of the Summit III prioritized action items is necessary to reduce the risk, severity, and consequences of concussion in the sport of ice hockey.